Regulatory reconstruction of ultra petita in industrial disputes: Aligning with justice principles - Gulo, Meilinus Adriganti Pelindung Hati; Sandi, Erdo Pramudya; Reza, Eka Octha; Yuniarti, Endang; Erawati, Wahyu Ririn; Andaryanti, Yuni; Mashdurohatun, Anis; Ariestawati, Navi; Nofrial, Ramon (Edelweiss Applied Science and Technology, 2025)
Judges play a crucial role in interpreting legal principles beyond written law to ensure justice, as outlined in Article 5 paragraph (1) of Law No. 48 of 2009. This principle allows judges to exercise discretion and align decisions with societal values of fairness, particularly in industrial disputes impacting individuals’ well-being. The study examines existing regulations for industrial dispute resolution, identifies weaknesses in achieving justice, and proposes reconstructing ultra petita principles to prioritize justice. Currently, Law No. 2 of 2004 governs industrial dispute resolution, emphasizing mediation or conciliation before proceeding to the Industrial Relations Court. Decisions from this court can only be challenged via cassation at the Supreme Court, as appellate procedures are absent. However, the justice system faces challenges as judges’ decisions often rely solely on statutory provisions, neglecting broader considerations of fairness, benefit, and legal certainty. Such limitations can exacerbate disputes and provoke controversy among stakeholders. The research highlights the need to reconstruct ultra petita principles to enable judges to deliver equitable and pragmatic decisions, even if they exceed the claims requested by parties. Although Article 178 paragraph (3) HIR and Article 189 paragraph (3) RBg assert the principle’s rigidity to ensure legal certainty, exceptions should be allowed to uphold justice. This approach reinforces the judiciary’s role as a forum for fairness and legal balance.